The Implementation of Telegram as A Pedagogical Tool to Enhance Student Motivation and Interaction - Kershnee Sevnarayan (Universitas Pendidikan Ganesha, 2023)
Despite efforts to understand how social media platforms encourage student interaction, researchers have noted that there needs to be more research that focuses on using Telegram messenger as a means to encourage student motivation and interaction in academic writing. This study aimed to understand how Telegram groups, created for first-year students at ODeL universities, increase student motivation and interaction in the Academic Writing module. This type of research is qualitative. This study uses a qualitative interpretative approach. Data collection techniques using interviews and observation. The subjects of this study were 4 lecturers and 9 students. The data analysis technique used is descriptive qualitative analysis. The study results found that lecturers considered Telegram a useful pedagogical tool to increase student motivation and interaction. Further findings reveal that Telegram motivates students to interact in groups and with modules. It is suggested that stakeholders reconsider their pedagogy and encourage using Telegram to assist students' learning of academic writing.